PERAN PENYULUH LAPANGAN TERHADAP KEBERHASILAN PETANI PADI LADANG DESA SUNGAI UPIH KECAMATAN KUALA KAMPAR - ", Sugianto; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Field extension workers have a strategic role in farmer income. This study aims to determine the role of field extension workers in field rice farmers in the achievement of rice barns in Sungai Upih Village, Kuala Kampar District, Pelalawan City. In this study the formulation of the problem is how the role of the field instructor to the rice farmers and the relationship between the extension agents influences the success of the rice farmers. Subjects in this study were rice farmers in Sungai Upih village, kuala Kampar district. Data collection techniques in this study were interviews, questionnaires and documentation. The method of population retrieval and samples was taken by taking 10% of the five blocks in the Sungai Upih village. From the role of field extension workers will help rice farmers in increasing rice farming income. The role extension officers also help farmers make good decisions and help farmers to improve farming. The effort to increase the production of field rice is the most important effort. The method used in this research is descriptive quantitative method. The results of this study indicate that field extension workers have a role in rice farmers 1). The role of field extension workers to provide knowledge to farmers, in providing knowledge to farmers extension workers have seven knowledge that must be given to rice farmers. 2). Field extension agents support and conduct activities for farmers, extension agents have five activities carried out on rice farmers. In the effort of farmers to increase the yield of field extension workers have a role to achieve towards the success of rice farmers also have a relationship and influence on the success obtained by rice farmers.Keywords: Sungai Upih, field extension, rice farmers